OPEN BUILDING CONCEPT FOR FISHERMAN HOUSING ON THE NORTH COASTAL SURABAYA (DIMENSI: Journal of Architecture and Built Environment, 2017)
One of global warming impacts is sea levels rising. Fisherman settlements on the North coastal Surabaya  is one of built enviromment that is affected by the threat from sea levels rising. Addtionally, this settlements faces severeal environmental problems including slums and housing density. Yet, this paper is limited only discussed the influence of fish processing activity area with the minimum housing area. The aim of study provides an alternative solution to these problems and to achieve feasible and sustainable fisherman settlements.  The descriptive qualitative is used as a research method. The field survey was used to obtain data for design concept supports. Results shows the current location has still fit as fisherman settlement, then the open building concept is proposed to redesign fisherman housings.  This design concept offers two aspects, namely adaptation and flexibility. The result shows that the concept of a vertical single housing unit in which  is owened by single (one) family, which is fit with the limited area, approximately 28 square meters.